MENTAL PREPARATION OF PREGNANT WOMEN AT HIGH RISK WITH PREGNANCY - Iin Tri Marlinawati (Departemen Psikiatri Fakultas Kedokteran Universitas Brawijaya, 2023)
Background: Pregnancy becomes risk period in woman’s life which need to make adjustment in physical and psychological. Improperhandling can cause serious problem. Women need to be readiness before entry to next phase become a mother.Objective: To reveal about mental readiness of pregnant women at high-risk pregnancy.Method: This paper was review which supported by literature review from PubMed, Medline and Cinahl database research published journal from 2017-2021 which talk about pregnant women at high-risk during pregnancy and the fetus.Results: 15-20% of pregnancies are high risk; pregnancies are complicated by the presence of a high risk or serious condition that affects the outcome of the mother and the fetuses. Women with high-risk pregnancies had 5.2x greater anxiety than women with low-risk pregnancies. High-risk pregnancies require more intensive or frequent treatments. Mental preparations need to be supported by many supporting system and holistic interventions.Conclusion: High-risk pregnancy and childbirth are two risk factors associated with anxiety during pregnancy. The mental preparation of pregnant women needs to be supported with adequate mental health to minimize adverse outcomes, maintain normal social relationshop and interactions, physical activity, oriented interventions to bring better quality of preparation. Keywords: mental, high-risk pregnancy, childbirth.